Getting the Customer Connected for Lifetime - Panda, Gitanjali; De, anmoy (Gyan Management Journal, 2007)
Vikram Dev was furious over the services of one of the telecom service provider in the state. It was Sunday morning, whe,:i Vikram received a call at his residence through the landline, from an old friend who informed him that he had been trying his mobile, but in vain. Prof Dev was confused. His friend’s query was con.finned, when he tried to make a call and no service was available over his mobile. The TVR message simply said, "The service to this number has been temporarily disconnected" Vikram Dev was using the services of one of the oldest and a leading cellular serv